(untitled) (Historia, 2021)
Are centenaries surely not the best times imaginable for fabrication, invention or otherwise making it up? Conventionally, it is nationalists who refract the history of their countries through heroic narratives - including tall stories - of one kind or another. Indeed, those sacrificial narratives of trial and tribulation have come to be anointed as the agent of history itself. While the pugnacious sentimentalism of South Africa’s woeful nationalists, past and present, has produced some first-class national fictions, one ought not to overlook impressive competition from various other places with a colonial past.